(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
Bullying is one of the serious problems in the world, where it can damage the physical and mental well-being of the parties involved. The problem of bullying cannot be ignored, especially in a school environment where at those ages a person is experiencing growth that is very important for their future. Prevention of bullying can also be done through activities in schools, one of which is the Pancasila Student Strengthening Project (P5) program. This research was conducted by describing findings in the field related to P5 activities in preventing bullying behavior. This research is descriptive research with a qualitative approach. Data collection through socialization (workshops), field observations, provision of diagnostic and formative assessments, and in-depth interviews with informants of research objects. Data analysis is carried out in stages of data reduction, data presentation, and conclusion drawing. Build their mind and body to be able to provide information about bullying so that participants can respond wisely in the future. The methods used are socialization (workshop), observation, discussion, brainstorming, challenges and project benefits. The selection of students at vocational schools as the object of research is due to the rampant bullying of students in schools